Doing Well by Doing Good: The Benevolent Halo of Corporate Social Responsibility - Chernev, Alexander; Blair, Sean (Journal of Consumer Research, 2015)
Abstract Corporate social responsibility is commonly viewed solely as a tool for enhancing company reputations and engendering goodwill among customers. In contrast, this research shows that the impact of corporate social responsibility can extend beyond public relations and customer goodwill to influence the way consumers evaluate a company’s products. Specifically, this research documents that acts of social goodwill—even when they are unrelated to the company’s core business, as in the case of charitable giving—can alter product perceptions, such that products of companies engaged in prosocial activities are perceived as performing better. More important, the data show that inferences drawn from a company’s prosocial actions are strong enough to alter the product evaluations even when consumers can directly observe and experience the product. The data further show that this effect is a function of the moral undertone of the company’s motivation for engaging in socially responsible behavior and is attenuated when consumers believe that the company’s behavior is driven by self-interest rather than by benevolence. By documenting that social goodwill can benefit consumer perceptions of product performance, these findings show that doing good can indeed translate into doing well.